Sains et saufs : petit manuel de lutte contre l'homophobie à l'usage des jeunes - Dorais, Michel; Verdier, Éric (VLB, 2005)
Section: 166, [10] pages ; 19 cm
Keywords: EDI; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; identités LGBTQIA2+; intervention sociale; justice sociale; premier cycle; psy4910; pédagogie; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences

Un parcours en contre point entre les sciences et les techniques, le féminisme et le genre - Fassa, Farinaz (Nouvelles Questions Feministes, 2005)
Number: 1 Publisher: Éditions Antipodes
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; inégalités; maternité; pays-bas; premier cycle; privilèges; pédagogie; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Whose Culture Has Capital? A Critical Race Theory Discussion of Community Cultural Wealth - Yosso, Tara J. (Race, Ethnicity and Education, 2005)
This article conceptualizes community cultural wealth as a critical race theory (CRT) challenge to traditional interpretations of cultural capital. CRT shifts the research lens away from a deficit view of Communities of Color as places full of cultural poverty disadvantages, and instead focuses on and learns from the array of cultural knowledge, skills, abilities and contacts possessed by socially marginalized groups that often go unrecognized and unacknowledged. Various forms of capital nurtured through cultural wealth include aspirational, navigational, social, linguistic, familial and resistant capital. These forms of capital draw on the knowledges Students of Color bring with them from their homes and communities into the classroom. This CRT approach to education involves a commitment to develop schools that acknowledge the multiple strengths of Communities of Color in order to serve a larger purpose of struggle toward social and racial justice.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; sciences de l'éducation; sex2283; thématiques; théorie critique de la race